Gen Alpha Slang in 'Last Rizzday Night' Lyrics: A Semantic Analysis - Subhan, Muhammad; Firdaus, Dadan; Yatmikasari, Ika (Journal of English Language and Education, 2025)
This study investigates the semantic evolution of Generation Alpha's slang as reflected in the lyrics of Jelly House's YouTube song Last Rizzday Night. As a digital-native generation, Gen Alpha frequently reshapes language through their engagement with digital media. Analysing 15 slang terms, including "Rizz," "Skibidi," and "Sigma," the research examines how their meanings align with or diverge from standard dictionary definitions. Using a qualitative descriptive methodology, the study highlights linguistic shifts driven by digital culture, such as "Rizz" symbolizing charm and social success, and "Sigma" representing self-reliant confidence. The findings emphasize the role of contextual semantics in understanding generational language trends, offering insights for educators, content creators, and marketers aiming to connect with Gen Alpha effectively.